2002
DOI: 10.1037/0022-0663.94.4.762
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating math development in Head Start classrooms.

Abstract: Teachers implemented a 6-week classroom intervention designed to promote emergent math skills and math interest in preschool-aged children. Teachers in experimental classrooms incorporated mathrelevant activities into their daily routine during circle time, transitions, mealtime, and small-group activities. Control classrooms engaged in their typical activities. After the program, experimental children scored significantly higher than control children on a standardized test of math ability and enjoyed math act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 71 publications
4
63
0
7
Order By: Relevance
“…En Amérique du Nord, une vaste proportion d'enfants issus de familles à faible revenu ne franchissent pas la maternelle munis de la structure cognitive centrale requise pour réussir en arithmétique dès la première année (Arnold, Fisher, Doctoroff et Dobbs, 2002 ;Entwisle et Alexander, 1990 ;Fuchs et al, 2001 ;Griffin et Case, 1996 ;Pagani, Larocque, Tremblay et Lapointe, 2003 ;Starkey et Klein, 2000). Comme le signalent les théories du développement, les jeunes enfants devraient percevoir le système numérique comme un concept dimensionnel, c'est-à-dire une ligne mentale numérique qui, précisément, leur permettra d'appliquer les stratégies arithmétiques appropriées (Case et Sowder, 1990 ;Griffin et al, 1994).…”
Section: Habiletés Numériques Et Classe Socialeunclassified
See 1 more Smart Citation
“…En Amérique du Nord, une vaste proportion d'enfants issus de familles à faible revenu ne franchissent pas la maternelle munis de la structure cognitive centrale requise pour réussir en arithmétique dès la première année (Arnold, Fisher, Doctoroff et Dobbs, 2002 ;Entwisle et Alexander, 1990 ;Fuchs et al, 2001 ;Griffin et Case, 1996 ;Pagani, Larocque, Tremblay et Lapointe, 2003 ;Starkey et Klein, 2000). Comme le signalent les théories du développement, les jeunes enfants devraient percevoir le système numérique comme un concept dimensionnel, c'est-à-dire une ligne mentale numérique qui, précisément, leur permettra d'appliquer les stratégies arithmétiques appropriées (Case et Sowder, 1990 ;Griffin et al, 1994).…”
Section: Habiletés Numériques Et Classe Socialeunclassified
“…Peu d'enfants inscrits à la maternelle bénéfi cient d'un programme d'éveil aux différentes manifestations du système numérique. Ceux qui en bénéfi cient déve-lopperont pourtant, en première année, une meilleure compréhension des nombres (Arnold et al, 2002), d'effi caces habiletés numériques (Griffi n, Case et Pick, 1998) et un intérêt pour les apprentissages à venir dans ce domaine (Stevenson et Newman, 1986).…”
Section: Habiletés Numériques Et Classe Socialeunclassified
“…Arnold, Fisher, Doctoroff, and Dobbs (2002) found that children receiving intervention not only improved their mathematics skills but also showed an increased interest in mathematics. Several studies (National Research Council, 2001;Stein, Remillard & Smith, 2007;Yang & Li, 2008) suggest that an opportunity to learn plays a key role in promoting low achieving students' mathematics performance.…”
Section: Remedial Instruction For Low-ses and Low-math Studentsmentioning
confidence: 99%
“…Por ejemplo, el Head Start Program en los Estados Unidos, ha enfatizado entre otros aspectos en el concepto de número en la intervención temprana (Arnold, Fisher y Dobbs, 2002). En España Miranda y Gil (2002) diseñaron un programa para la educación prescolar con el fin de estimular la comprensión del concepto de número y el uso del juego y la narración en la adquisición de los conceptos matemáticos básicos.…”
unclassified